Conversation analysis in social work research: a scoping review. (November 2022) - Flinkfeldt, Marie; Iversen, Clara; Jørgensen, Sabine Ellung; Monteiro, David; Wilkins, David
Given the emphasis on communication in social work, the empirical study of social work interactions is an important area for research. By examining recordings of naturally occurring social interaction and analysing participants' practices in close detail, conversation analysis (CA) provides rigorous resources for understanding the practical challenges and opportunities of professional intervention. Since the origins of CA in the 1970s, this approach has been used for investigating interactions in a wide range of institutional domains. Based on articles published in peer-reviewed journals in English, this scoping review maps the development of CA in social work research. The review gives an overview of the institutional contexts, professional groups and client groups that have been investigated using CA methods, as well as how their interactional practices have been examined. We show contributions of CA to understanding social work in terms of specific interactional practices, how practitioners accomplish challenging institutional activities in interactions and how theories and ideals about interactions relate to social work practice. The review highlights research gaps concerning clients' resources for pursuing agendas, embodied conduct in social work, contributions to the cumulative body of CA research and implications for practice. We discuss these findings in relation to CA as a relatively new approach in social work research and the challenges which CA may need to address to become a more integrated part of social work research and practice.